Early mortality in systemic vasculitis: relative contribution of adverse events and active vasculitis. Issue 6 (1st July 2009) - Little, Mark A; Nightingale, Peter; Verburgh, C A; Hauser, Thomas; De Groot, Kirsten; Savage, Caroline; Jayne, David; Harper, Lorraine
Abstract : Objective: To contrast the effect of the burden of vasculitis activity with the burden of adverse events on 1-year mortality of patients with antineutrophil cytoplasmic antibody-associated vasculitis (AAV). Methods: This study assessed the outcome and adverse events in patients prospectively recruited to four European AAV clinical trials. Data on 524 patients with newly diagnosed AAV were included. The burden of adverse events was quantified using a severity score for leucopenia, infection and other adverse events, with an additional weighting for follow-up duration. A 'combined burden of events' (CBOE) score was generated for each patient by summing the individual scores. Vasculitis severity was quantified using the Birmingham vasculitis activity score and glomerular filtration rate (GFR). Results: 1-year mortality probability was 11.1%; 59% and 14% of deaths were caused by therapy-associated adverse events and active vasculitis, respectively. Using Cox regression analysis, infection score (p<0.001), adverse event score (p<0.001), leucopenia score (p<0.001) and GFR (p=0.002) were independently associated with mortality. The risk of 1-year mortality remained low (5%) with CBOE scores less than 7, but increased dramatically with scores above this. Hazard ratio for death with a CBOE greater than 7 was 14.4 (95% CI 8.4 to 24.8). Age and GFR were independent predictors of CBOE score. Conclusions: The greatest threat to patients with AAV in the first year of therapy is from adverse events rather than active vasculitis. The accumulation of adverse events, monitored using this scoring method, should prompt increased awareness that the patient is at high risk of death.